Climate crisis and displacement – from commitment to action - Bilak, A; Kälin, W (University of Oxford, 2022)
Significant progress has been made in focusing international attention on the need to address displacement in the context of disasters and the adverse effects of climate change. Despite a wide range of global policy frameworks, however, actions being taken are not yet having a sufficiently deep and far-reaching impact.